Core clinical competencies in anesthesiology : a case-based approach - Gallagher, Christopher J.; Lewis, Michael (Michael C.); Schwengel, Deborah A; Cambridge eBooks (Cambridge : Cambridge University Press, 2010)
The core clinical competencies in anesthesiology can be pretty blurry - just how do they apply to real life? This book answers this question, incorporating the core clinical competencies into an engaging format that anesthesiologists like - case studies. So, far from being a 'dry and dusty volume of forgotten lore', this book actually makes learning the competencies fun! Written in the same engaging style as a number of other anesthesia books (specifically, the Board Stiff opus) by leading anesthesiologists from leading medical centers across the United States, this book will bring the core clinical competencies to life for medical students.
Contributions from Stony Brook University Medical Center under Christopher J. Gallagher -- Contributions from the University of Medicine and Dentristy of New Jersy under Steven H. Ginsberg -- Contribution from the University of Texas M.D. Anderson Cancer Center under Marc Rozner -- Contributions from the University of Miami Miller School of Medicine under Michael C. Lewis -- Contributions from Johns Hopkins Medical Institutions under Deborah A. Schwengel -- Contribution from the Medical College of Wisconsin under Elena J. Holak.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Anesthesia -- Case studies; Electronic books